The 'Four Pathways' Madrasah Principal's Strategy Management In Improving Teacher Commitment - Kurniawati, Ria; Badarussyamsi, Badarussyamsi; Syukri SS, Ahmad (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article discusses the strategic management carried out by the Head of Madrasah Aliyah Batam State, Riau Islands Province to increase teacher commitment. The main problem studied is how is the strategic management carried out by the Head of MAN Batam to increase teacher commitment? The research method used is a qualitative-descriptive method, with data collection through observation, interviews and documentation. The research results show that the Head of MAN Batam has implemented the principles of strategic management which consist of environmental observation, both internal and external observation, then strategy formulation, strategy implementation and evaluation. The state of teacher commitment at MAN Batam is divided into two forms of commitment, namely, commitment to carrying out their duties and commitment to improving the quality of madrasahs. The implementation of strategic management carried out by the Head of MAN Batam to increase teacher commitment is divided into three major plans; optimizing school management, optimizing the role of school principals, and optimizing efforts to create committed professional teachers. Artikel ini membahas tentang manajemen strategi yang dijalankan oleh Kepala Madrasah Aliyah Negeri Batam Provinsi Kepulauan Riau untuk meningkatkan komitmen guru. Permasalahan utama yang dikaji adalah bagaimana manajemen strategi yang dilakukan Kepala MAN Batam untuk meningkatkan komitmen guru? Metode penelitian yang digunakan adalah metode kualitatif-deskriptif, dengan pengkumpulan data secara observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa Kepala MAN Batam telah melaksanakan prinsip-prinsip manajemen strategi yang terdiri dari pengamatan lingkungan, baik pengamatan internal maupun eksternal, kemudian perumusan strategi, pelaksanan strategi, dan evaluasi. Keadaan komitmen guru di MAN Batam dibagi ke dalam dua bentuk komitmen yakni, komitmen di dalam menjalankan tugas dan komitmen dalam meningkatkan kualitas madrasah. Adapun implementasi manajemen strategi yang dijalankan oleh Kepala MAN Batam untuk meningkatkan komitmen guru dibagi ke dalam tiga rancangan besar; optimalisasi manajemen sekolah, optimalisasi peran kepala sekolah, dan optimalisasi upaya penciptaan guru profesional yang komit.